VACUUM-ASSISTED CLOSURE IN THE TREATMENT OF STERNAL WOUND INFECTION AFTER CARDIAC SURGERY - Simek, Martin; Nemec, Petr; Zalesak, Bohumil; Kalab, Martin; Hajek, Roman; Jecminkova, Lenka; Kolar, Milan (Biomedical papers, 2007)
Aim: Vacuum-assisted closure (VAC) was primarily designed for the treatment of pressure ulcers or chronic, debilitating wounds. Recently, VAC has become an encouraging treatment modality for sternal wound infection after cardiac surgery, providing superior results to conventional treatment strategies.Methods: From November 2004 to September 2006, 34 patients, undergoing VAC therapy for sternal wound infection following cardiac surgery, were prospectively evaluated. Ten patients (29 %) were treated for superficial sternal wound infection and 24 (71 %) for deep sternal wound infection. The median age was 69.9 years (range 48 to 82) and the median BMI was 33.4 kg/m2 (range 28 to 41). Twenty patients (59 %) were women and 19 patients (59 %) were diabetics. Owing to sternal wound infection complications, 16 patients (47 %) were readmitted to the department. VAC was used following the previous failure of the conventional treatment strategy in 7 patients (21 %).Results: Thirty-three patients (97 %) were treated successfully. One patient (3 %) died of multiple organ failure. The overall length of hospitalization was 34.6 days (range 9 to 62). The median number of dressing changes was 4.6 (range 3 to 10). The median VAC treatment time until surgical closure was 9.2 days (range 6 to 21 days). VAC therapy was solely used as a bridge to definite wound closure. Three patients (9 %) with chronic fistula were re-admitted 1 to 6 months after VAC therapy.Conclusions: VAC therapy is a safe and reliable option in the treatment of sternal wound infection in cardiac surgery. VAC therapy should be considered an effective adjunct to conventional treatment modalities for the treatment of extensive and life-threatening wound infections following cardiac surgery, particularly in the presence of risk factors.
Keywords: Vacuum assisted closure/Sternal wound infection/Cardiac surgery